Pemenuhan Hak Penghasilan Pekerja Rumahan Sektor Usaha Alas Kaki Di Muara Baru Jakarta Utara DKI Jakarta - Abdul Husen; Abdullah Sulaiman (Faculty of Sharia and Law State Islamic University Syarif Hidayatullah Jakarta, 2022)
This home worker in the Muara baru area of North Jakarta is one of the informal sector workers who are still not regulated in Law Number 13 year 2003 concerning Manpower. The situation causes homeworkers have not received recognition and certainty of their work status, they often forgotten in manpower planning policies and have to deal with various obstacles as workers, including the non-fulfillment of their rights as workers in Indonesia. This thesis aims to find out how the mechanism should be taken to ensure the fulfillment of the rights of homeworkers in the regions Muara Baru, North Jakarta and what is the government's role in providing legal protection of the home work system in Indonesia in general and in Muara Baru area, North Jakarta in particular, by knowing in advance how is the legality of work agreements made between homeworkers in the regions Muara Baru, North Jakarta with an employer intermediary. This research using the type of empirical juridical research by conducting interviews fieldwork for homeworkers in the Muara Baru area of North Jakarta, then conduct a study of library materials by reading, studying, review and analyze the literature to develop related studies with the title of this thesis. The results of this study indicate that the legality of the work agreement established between homeworkers in the Muara Baru area of North Jakarta with intermediaries the employer is only limited to a verbal work agreement, while the mechanism must be done in order to create guarantees for the fulfillment of the rights of homeworkers in the regions Muara Baru North Jakarta is through the mobilization of law and the Government in this has not yet come into play. In order to prevent this from happening prolonged, it is necessary to revise Law Number 13 Year 2003 concerning Manpower or the enactment of new Laws and Regulations related to the work-home system.